PENGEMBANGAN E-MODUL BERBASIS CANVA MELALUI PENDEKATAN STEAM UNTUK MENINGKATKAN KEMAMPUAN NUMERASI MATEMATIS SISWA - Ruizhaica Agustina; Yumira Simamora; Khoiruddin Matondang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Canva-based e-module through the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach to improve students' mathematical numeracy skills. The research employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate), with the dissemination stage conducted on a limited basis. The subjects were 10th grade students of MA Al Washliyah Tanjung Beringin, involving individual testing (6 students), small group testing (10 students), and field testing (30 students). The instruments used were expert validation sheets, practicality questionnaires, and numeracy tests. The results indicate that the developed e-module meets validity criteria, with average scores from media experts (0.83), material experts (0.73), post-test (1.0), and teaching module (0.78), all categorized as valid. The practicality results show scores of 87.5% from teachers and 83.5% from students, indicating a very practical category. The effectiveness is reflected in the increase of classical learning completeness from 70% in small group testing to 80% in field testing, exceeding the minimum passing grade of 75. Thus, the Canva-based e-module using the STEAM approach is proven to be valid, practical, and effective in improving students’ mathematical numeracy skills.